(untitled) (Vallis Aurea, 2024)
Purpose: The purpose of this study is to revitalize the freshwater ponds by assessing physical structures, water quality parameters and sustainable bio- recharging strategies through community engagement. Research Design: The study employs a combination of exploratory and descriptive research approaches. Sampling was conducted among the individuals who are in direct access with the freshwater ponds. Methodology: Data collection involved direct surveys using a structured questionnaire and the water samples were collected from the selected regions Results: The results reveal that there are ponds that need immediate restoration and rejuvenation in order to sustainably take up the matter of a balanced ecosystem for the better survival and coexistence of individual species along with mankind by proper maintenance of the water body for a better tomorrow. The water quality analysis shows significant causes of deterioration due to ecological instability and overuse of the resources by improper management strategies which resulted in loss of biodiversity and habitat loss. Originality of Research: This study records the revitalization of freshwater ponds by assessing physical structures, water quality parameters, and sustainable bio- recharging strategies through community engagement.